1998
DOI: 10.1002/(sici)1096-8628(19980724)78:4<336::aid-ajmg6>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Population and family studies of dihydropyrimidinuria: Prevalence, inheritance mode, and risk of fluorouracil toxicity

Abstract: To evaluate the prevalence of dihydropyrimidinuria (DHPuria), we analyzed urine samples from 21,200 healthy Japanese infants, and found two cases of DHPuria without clinical symptoms. Based on this result, we estimated the prevalence to be approximately 1/10,000 births in Japan. In addition, we analyzed pyrimidine catabolism on a previously reported family with an adult DHPuria case. We newly identified the sister of the propositus as the second case of DHPuria in this family, because she excreted large amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 7 publications
0
33
1
Order By: Relevance
“…Deficiency of DHP is a rare inborn error of the pyrimidine degradation pathway, with only around 20 11 after analysing urine samples from 21 200 healthy Japanese infants, two asymptomatic cases of dihydropyrimidinuria were encountered. The authors suggested that in Japan, the estimated prevalence of the deficiency was approximately 1/10 000.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deficiency of DHP is a rare inborn error of the pyrimidine degradation pathway, with only around 20 11 after analysing urine samples from 21 200 healthy Japanese infants, two asymptomatic cases of dihydropyrimidinuria were encountered. The authors suggested that in Japan, the estimated prevalence of the deficiency was approximately 1/10 000.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that in Japan, the estimated prevalence of the deficiency was approximately 1/10 000. 11 The clinical phenotype of patients with DHP deficiency is highly variable. Notably, this disorder has also been reported in asymptomatic individuals identified by population screening for pyrimidine metabolism disorders 9,10 or family screening of relatives of DHP deficiency patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymes of the pyrimidine degradation pathway consist of dihydropyrimidine dehydrogenase (DPD), DHP, and b-ureidopropionase (UP). As these enzymes are also involved in the activation and degradation of the widely used antineoplastic drug 5-fluorouracil (5-FU), a deficiency of one of these enzymes has been considered to be clinically important for the risk of severe toxicity after a treatment with 5-FU (Sumi et al 1998;Van Kuilenburg et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only 28 patients have been described with DHP deficiency caused by autosomal recessive defects of the DPYS gene (OMIM 222748), and 5 of these patients were symptomless individuals who were identified by a screening program (Assmann et al 1997;Duran et al 1990Duran et al , 1991Hamajima et al 1998;Henderson et al 1993;Ohba et al 1994;Putman et al 1997;Sumi et al 1996Sumi et al , 1998Van Gennip et al 1997;Van Kuilenburg et al 2007. The prevalence of human DHP deficiency in Japan has been estimated to be 1 in 10,000.…”
Section: Introductionmentioning
confidence: 99%